Child Athletes and Athletic Objectification. (June 2017) - Cameron, Nadine; McPherson, Lynne; Atkins, Prue; Nicholson, Matthew; Long, Maureen
This article examines the risks associated with conceptualizing the child athlete's body primarily in aesthetic terms and as an instrument of sporting victory, and develops a concept of "athletic objectification." It draws on a recent research project involving Australian males and females aged between 18 and 25 who participated in organized sport as children. It identifies socially prevalent beliefs and values to which the athletic objectification of children may be partially attributed. These include the orthodoxy that sport is inherently good for children's development, and the particular valorization of sporting success and gendered expectations that characterize Western society. It concludes with the argument that serving children's best interests in sport requires that their broader psychosocial needs are given priority above the short-term development of their athletic capacity.